STRUKTUR KOMUNITAS FITOPLANKTON SEBAGAI BIOINDIKATOR STATUS TROFIK PERAIRAN WADUK JANGARI KABUPATEN CIANJUR - Intan Suhartini; Isma Dwi Kurniawan; Rahmat Taufiq M.A (Gunung Djati Conference Series, 2021)
Jangari Reservoir is one of the edges of the CirataReservoir located in West Java. Jangari Reservoir is widely usedas tourism and a place for fish cultivation which has the potentialto improve the trophic status of the waters. Phytoplanktoncommunities can be used as bioindicators in evaluating the trophicstatus of waters. This study aims to determine the trophic status ofthe Jangari Reservoir by using phytoplankton as a bioindicatorcombined with the physical and chemical properties of the waters.The method used is purposive sampling by determining threestations based on differences in utilization, tourism activities andfloating net cages. The data analysis consisted of the structure ofthe phytoplankton community and the calculation of the TrophicLevel Index (TLI) value. The physical and chemical parameterstested included water temperature, brightness, salinity, DO, pH,Total Nitrogen (TN), and Total Phosphorus (TP). The resultsshowed that there were 10 classes of phytoplankton found,consisting of Bacillariophyceae (3 genus), Chlorophyceae (7 genus), Cyanophyceae (1 genus), Dinophyceae (2 genus),Euglenophyceae (1 genus), Mediophyceae (2 genus),Trebouxiophyceae (3 genus), Ulvophyceae (1 genus),Xanthophyceae (1 genus), and Zygnematophyceae (3 genus).Abundance of phytoplankton ranged from 2,078-2,896 ind/L.Concentration of chlorophyll-a ranged from 22.5 to 31.96 mg/L.Value of the TLI ranged from 4.34 to 4.58. Based on observations,the trophic status of Jangari Reservoir based on phytoplanktoncomposition is classified as eutrophic, based on abudance ismesotrophic, and based on TLI is eutrophic.